The mechanism of square dancing on subjective well-being among middle-aged and older women in China: mediating role of social connectedness and moderating role of exercise self-efficacy - Wang, Junmin; Wu, Qingzhong; Xi, Yongping; Xia, Hongtao (Frontiers in Public Health, 2025)
ObjectiveThis study investigates how participation in square dancing influences subjective well-being among middle-aged and older women, focusing on the mediating role of social connectedness and the moderating role of exercise self-efficacy.MethodsA cross-sectional survey of 365 middle-aged and older women engaged in square dancing was conducted. Validated questionnaires were used to assess square dancing participation, social connectedness, exercise self-efficacy, and subjective well-being. Structural equation modeling and moderated mediation analyses were employed to test the hypothesized model.ResultsParticipation in square dancing was positively associated with the subjective well-being of middle-aged and older women (β = 0.252, p < 0.001), and this association was partially mediated by social connectedness (β = 0.175, p < 0.001, 40.98% of the total effect). Moreover, exercise self-efficacy moderated both the link between square dancing and social connectedness (β = 0.182, p < 0.001) and the direct link between square dancing and subjective well-being (β = 0.122, p < 0.001), indicating a dual moderating role.ConclusionMiddle-aged and older women who participate in square dancing not only directly enhance their subjective well-being but also indirectly improve it by strengthening their sense of social connectedness. Furthermore, individuals with higher levels of exercise self-efficacy experience more pronounced gains in social connectedness and subjective well-being through square dancing activities.